Bilgi Bilimi Eğitiminde Yeni Eğilimler ve Türkiye’de Eğitim Veren Bilgi ve Belge Yönetimi Bölümleri Müfredatlarının IFLA Temel Bilgi Alanlarına Göre Analizi. - Polat, Coşkun; Faydalıgül, Özden Demircioğlu (Journal of the Institute of Social Sciences Cankiri Karatekin University / Çankırı Karatekin Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2024)
Purpose: The aim of this study is to determine the current trends in library and information science education, which diversifies and changes direction over time, to evaluate the curricula of the Information Management Departments providing education in this field in Turkey within the scope of the Foundational Knowledge Areas created by IFLA, and to reveal the similarities and differences in the curricula of the departments. Method: Content analysis was used as a method in the study. Firstly, attempts have been made to detect new trends in education in this field by examining the relevant literature, the subjects included in the iSchools common curriculum and the IFLA Guidelines for Professional Library and Information Science Education Programs. The content analysis and comparison of the undergraduate curricula of fourteen information and documentation departments providing active education in Turkey were made according to the curriculum recommended by this guide prepared by IFLA. For this purpose, separate fields were defined for compulsory and elective courses in data sets created in a separate MS Excel program for each department. Courses are grouped according to the three main field requirements specified in the guide. Foundational Knowledge Area coding of the grouped courses was done according to the ECTS description. After coding, comparative analysis was made within each section and between sections. All calculations and operations related to the tables were also carried out via the Excel program. Findings: As a result of the analysis, the weighted main areas of each department and the distribution of the courses in the Foundational Knowledge Areas were revealed. It was understood that the departments included courses in the Core areas of Technical and Management, User Services and LIS Foundations in their curricula, respectively. Conclusion: In the study, it was found that the departments should structure their curricula according to the new trends in the field of Library and Information Science determined within the scope of the literature review. There is an imbalance in the distribution of Foundational Knowledge Areas in the curricula of Information Management departments which provide education in Turkey. According to the findings of the study, a common curriculum with balanced courses covering the Foundational Knowledge Areas, and a consortium of Information Schools Organization were proposed. Originality: This study differs from other studies by being the first study to analyze the content of the curricula of information management departments that provide education in Turkey according to the Foundational Knowledge Areas recommended by IFLA and by presenting an up-to-date course curriculum proposal in line with the Foundational Knowledge Areas.